ECONOMIC BURDEN OF CARDIOVASCULAR DISEASES IN RYAZAN' REGION - S. S. Yakushin; E. V. Filippov (Российский кардиологический журнал)
Aim. To evaluate economical costs of CVD in Ryazan' Region. Material and methods. The counting of economical expenses was done according to the data of the official statistics, and to the data of the MERIDIAN-RO study (quantity of disabled, their economical and social parameters, quantity of disability certificates and their main reasons during last year before the study). All data provided with accordance to the computation methodology of economical toll from mortality, morbidity and disability of citizens, that is ratified by the Ministry of Economics and Development, the Ministry of Health and Social Development, RosStatistics from 10.04.2012 #192/323n/45n/113.Results. After calculation of nondirect toll from CVD in Ryazan' Region it was shown that it is 4,9% GRP. In Ryazan' Region more than a half (54,7%) of all nondirect toll from CVD is kinked to mortality, all other toll is equally spread to disability (23%) and morbidity (22,3%).Conclusion. Nondirect economic toll from CVD in Ryazan' Region are very high and in 2012 reached 1805767093,09 RUR (that is equal 4,9% VRP). The main impact is from mortality (54,7%). It requires the activation of prevention and treatment strategies for the decrease of mortality in Ryazan' Region. Also the imrovement of statistics required and of efficacy of prevention programs evaluation.